Macitentan Improves Health-Related Quality of Life for Patients With Pulmonary Arterial Hypertension: Results From the Randomized Controlled SERAPHIN Trial - Mehta, Sanjay; Sastry, Bhagavatula Kutumba Srinivasa; Souza, Rogério; Torbicki, Adam; Ghofrani, Hossein-Ardeschir; Channick, Richard N; Delcroix, Marion; Pulido, Tomás; Simonneau, Gérald; Wlodarczyk, John; Rubin, Lewis J; Jansa, Pavel; et al. (Chest, 2017)
BACKGROUND: Pulmonary arterial hypertension (PAH) leads to reduced health-related quality of life (HRQoL). The objectives of this analysis were to evaluate the effect of macitentan on HRQoL in patients with PAH in the Study with an Endothelin Receptor Antagonist in Pulmonary Arterial Hypertension to Improve Clinical Outcome (SERAPHIN) study. The association between baseline HRQoL and long-term outcomes was also investigated. METHODS: Patients were randomized to placebo, macitentan 3 mg, or macitentan 10 mg once daily. Patients aged 14 years or older completed the 36-Item Short Form Survey (SF-36) at baseline, at month 6 and month 12, and at the end of treatment (EOT). The absolute change from baseline to month 6 in SF-36 scores was calculated. The time to a clinically meaningful deterioration in the SF-36 physical component summary and mental component summary (PCS and MCS) scores and associations between baseline PCS/MCS scores and time to morbidity/mortality events were also assessed. RESULTS: At month 6, macitentan 10 mg significantly improved seven of eight SF-36 domains and the PCS and MCS scores vs placebo. Macitentan 10 mg significantly reduced the risk of a three-point or greater deterioration in PCS (hazard ratio [HR], 0.60; 95% CI, 0.47-0.76; P < .0001) and MCS scores (HR, 0.76; 95% CI, 0.61-0.95; P = .0173) until EOT vs placebo. Patients with a baseline PCS score greater than the median baseline value had a significantly reduced risk of morbidity/mortality compared with patients with a PCS score less than the median; a similar result was observed for the MCS score. CONCLUSIONS: Macitentan significantly improved HRQoL in patients with PAH compared with placebo and significantly reduced the risk of a clinically meaningful HRQoL deterioration. An association between better baseline HRQoL and improved long-term outcomes was shown. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00660179; URL: clinicaltrials.gov.
Keywords: pharmacotherapy; Drug Monitoring; Humans; posouzení stavu pacienta; health-related quality of life; antagonisté endotelinového receptoru B; lidé středního věku; pyrimidiny; monitorování léčiv; Quality of Life; Dose-Response Relationship, Drug; Female; Patient Acuity; dospělí; sulfonamidy; výsledek terapie; lidé; Hypertension, Pulmonary; kvalita života; Adult; plicní hypertenze; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Endothelin B Receptor Antagonists; vztah mezi dávkou a účinkem léčiva; Pyrimidines; mužské pohlaví; pulmonary arterial hypertension; Sulfonamides